2015
DOI: 10.1681/asn.2014090875
|View full text |Cite
|
Sign up to set email alerts
|

Combined Deletion of Vhl and Kif3a Accelerates Renal Cyst Formation

Abstract: A subset of familial and sporadic clear cell renal cell carcinomas (ccRCCs) is believed to develop from cystic precursor lesions. Loss of function of the von Hippel-Lindau tumor suppressor gene (VHL) predisposes renal epithelial cells to loss of the primary cilium in response to specific signals. Because the primary cilium suppresses renal cyst formation, loss of the cilium may be an initiating event in the formation of ccRCC. To test this hypothesis, we analyzed the consequences of inducible renal epithelium-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 43 publications
3
26
0
Order By: Relevance
“…Multiple groups have now demonstrated that Vhl inactivation either in the germline or by conditional inactivation in the kidney results in only a mild increase in rate of renal cyst formation2638394041. While the addition of secondary genetic events such as Pten or Kif3a loss appear to accelerate the cystic phenotype induced by Vhl inactivation, they do not result in frank neoplasia4243. Combined inactivation of Vhl with Trp53 does appear to induce renal tumours, which have clear cell changes but not bona fide clear cell RCC histology44.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple groups have now demonstrated that Vhl inactivation either in the germline or by conditional inactivation in the kidney results in only a mild increase in rate of renal cyst formation2638394041. While the addition of secondary genetic events such as Pten or Kif3a loss appear to accelerate the cystic phenotype induced by Vhl inactivation, they do not result in frank neoplasia4243. Combined inactivation of Vhl with Trp53 does appear to induce renal tumours, which have clear cell changes but not bona fide clear cell RCC histology44.…”
Section: Discussionmentioning
confidence: 99%
“…5) argues that ccRCC formation requires mutations in addition to VHL. There are currently no autochthonous mouse models that fully reproduce all of the characteristic morphologic and invasive properties of human ccRCC; however, consistent with the hypothesis that multiple cooperating mutations are required for ccRCC development, kidney epithelial cell-specific codeletion of Vhl with Pten (6), or with Kif3a to genetically ablate primary cilia (7), caused the formation of simple and atypical cystic lesions that are similar to the ccRCC precursor cystic lesions found in the kidneys of patients with inherited VHL disease. Deletion of Vhl together with homozygous loss of Trp53 (8) or with heterozygous loss of Bap1 (9) gave rise to very similar phenotypes, including simple and atypical cystic lesions as well as tumors containing cells that display cytoplasmic clearing and elevated mTORC1 activity, recapitulating many of the cellular and molecular changes that are characteristic of human ccRCC.…”
Section: Introductionmentioning
confidence: 91%
“…Ciliogenesis is regulated by pVHL [16], pVHL and glycogen synthase kinase-3β (GSK3β) together regulate cilium maintenance [17], and pVHL has been shown to act as a microtubule stabilizer [18]. Even so, it remains unclear if these functions of pVHL are HIF-regulation independent, as recent knockout experiments have shown that HIF-1α is not involved in renal cyst growth [19]. Regarding potential direct interactions between HIF and cilia, recent results show that prolyl hydroxylase inhibition of HIF-2α leads to HIF-2α accumulation within the cilia [20] and deubiquintination of HIF-1α is essential for ciliogenesis [21].…”
Section: Introductionmentioning
confidence: 99%